DETERMINAN MAKRO DAN MIKRO PENYERAPAN TENAGA KERJA SEKTOR INFORMAL DI INDONESIA - Ilham Nugraha; Sutyastie Sumitro; Eva Ervani (Media Ekonomi, 2025)
Indonesia’s demographic dividend presents an opportunity for economic growth, yet its potential is constrained by persistently high labor informality. This study analyzes the micro- and macro-level determinants of informal employment in Indonesia. This study applies a quantitative multilevel approach by combining microdata from the 2024 National Labor Force Survey (Sakernas) with provincial panel data for 34 provinces over the period 2020–2024. A binary logistic regression is used to examine individual-level determinants of informal employment, while a fixed effects model estimates the impact of regional economic growth, minimum wages, ICT skills, and the number of established entrepreneurs. At the micro level, education, age, gender, marital status, and place of residence significantly influence the likelihood of informal employment. Higher education reduces informality, while older age and rural residence increase it. At the macro level, economic growth is positively associated with informal employment, indicating that growth has not yet translated into inclusive formal job creation. ICT skills significantly reduce informality, while minimum wages show no significant effect. The number of established entrepreneurs negatively affects informal employment, suggesting that business maturity supports labor formalization. Overall, labor informality in Indonesia is shaped by the interaction between individual characteristics and regional structural factors.